2013
DOI: 10.1167/iovs.12-9680
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Processing of Scene Context in Macular Degeneration

Abstract: Our results suggest that when central vision is impaired (as in AMD), the contextual information captured by peripheral vision provides cues for object categorization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…People with AMD are reported to recognise isolated objects better than objects in scenes, coloured images better than achromatic images,61 recognise an object in a scene more easily when enhanced with a border62 and when placed on a related compared to an unrelated background 63. AMD has been shown to affect processing of high-spatial frequency scenes 64.…”
Section: Resultsmentioning
confidence: 99%
“…People with AMD are reported to recognise isolated objects better than objects in scenes, coloured images better than achromatic images,61 recognise an object in a scene more easily when enhanced with a border62 and when placed on a related compared to an unrelated background 63. AMD has been shown to affect processing of high-spatial frequency scenes 64.…”
Section: Resultsmentioning
confidence: 99%
“…This memory-based knowledge could also be more effective for prototypical scenes including hazards with high (vs. medium) braking affordance. Previous research has shown how scene gist is acquired from information across the entire scene and not only at central vision (Boucart, Moroni, Szaffarczyk, & Tran, 2013;Boucart, Moroni, Thibaut, Szaffarczyk, & Greene, 2013;Boyce & Pollatsek, 1992;Larson, Freeman, Ringer, & Loschky, 2014;Larson & Loschky, 2009;Li, VanRullen, Koch, & Perona, 2002;Thorpe et al, 2001). However, whereas the present data can be explained without referring to gist processing (see above), the assessment of the role of gist in peripheral hazard perception clearly calls for dedicated empirical tests (involving gist previews along with moving window techniques) in future research, probably involving more controlled material such as panoramic scenes with or without hazards at a wide variety of eccentricities.…”
Section: Discussionmentioning
confidence: 99%
“…scotoma (e.g., in macular degeneration), implicit processing of contextual information (the background) in peripheral vision facilitates central object categorization (Boucart, Moroni, Szaffarczyk, & Tran, 2013a). Previous studies of peripheral vision at very large eccentricities (beyond 508) have shown that normally sighted young observers are above chance at detecting animals in photographs of natural scenes at 758 eccentricity (Thorpe, Gegenfurtner, Fabre-Thorpe, & Bulthoff, 2001).…”
Section: Introductionmentioning
confidence: 99%